Conversion of silent synapses to AMPA receptor-mediated functional synapses in human cortical organoids - Masatoshi Nishimura; Tomoki Kodera; Shota Adachi; Akinori Y. Sato; Ryosuke F. Takeuchi; Hiroshi Nonaka; Itaru Hamachi; Fumitaka Osakada (Neuroscience Research, 2025)
Despite the crucial role of synaptic connections and neural activity in the development and organization of cortical circuits, the mechanisms underlying the formation of functional synaptic connections in the developing human cerebral cortex remain unclear. We investigated the development of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-mediated synaptic transmission using human cortical organoids (hCOs) derived from induced pluripotent stem cells. Two-photon Ca2⁺ imaging revealed an increase in the frequency and amplitude of spontaneous activity in hCOs on day 80 compared to day 50. Additionally, spontaneous neural activity in late-stage hCOs, but not in early-stage hCOs, was blocked by N-methyl-D-aspartate receptor (NMDAR) and AMPAR antagonists. However, transsynaptic circuit tracing with G-deleted rabies viral vectors indicated a similar number of synaptic connections in early- and late-stage hCOs. Notably, chemical labeling demonstrated a significant increase in AMPAR expression on the postsynaptic membrane and colocalization with NMDARs in late-stage hCOs. These results suggest that hCOs progressively organize excitatory synaptic transmission, concurrent with the transition from silent synapses lacking AMPARs to functional synapses containing NMDARs and AMPARs. This in vitro model of human cortical circuits derived from induced pluripotent stem cells reflects the developmental programs underlying physiological transitions, providing valuable insights into human corticogenesis and neurodevelopmental disorders.